Politeness Speech on Solidarity Scale-Based Manado Malay Speakers - Thelma I. M. Wengkang; Thomas M. Senduk (Jurnal Lingua Idea, 2021)
This study aims to describe the form and meaning of politeness speech on solidarity scale-based Manado Malay speakers. This study conducted in Manado city and used qualitative as a method. Observation and interviews were used as a technique of the study. The observation was used to observe the speakers of Manado Malay in using polite speech in daily social activities, whereas an interview was used by the researcher to questioning the informant about the use of polite speech in social interaction. This technique is complemented with listening, proficient, and note-taking techniques. The researcher plays a role as a key instrument who collects and analyzes the data. The source of data is the native speakers of Manado Malay who do interact in various places. Three informants who master Manado Malay were chosen. Techniques of analyzing data consist of 1) data reduction, simplified data collection, 2) data presentation, simplified data presented, categorized based on form and meaning, 3) verification, the data that has been presented were checked once more to ensure the accuracy according to the expected data, 4) conclusions, answering the predetermined problem formulations. The results showed that the social dimension, especially the solidarity scale, is a consideration for Manado Malay speakers in realizing polite speech, as well as when to use informal variants and when to use formal ones. The relationship among speakers has made them create the appropriate language choices, but language ethics that embody politeness remain a consideration. In various social interactions, occupations, religious meetings, associations, and family interactions, it turns out that Manado Malay people realize the politeness of speaking by changing command sentences into declarative sentences and asking along with the use of a flat intonation when speaking. The consideration of solidarity is the reason they speak politely, in addition to the status and formality scale.